(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article provides information on the cultivation of Tilapia (Oreochromis mossambicus) in various types of water in the conditions of Karakalpakstan. Research work was carried out in 3 different water bodies, namely geothermal springs, closed water circulation systems, and artificial reservoirs, and their chemical composition was determined. During the research work, the average body weight of fish and the ratio of their caviars to body weight were determined in different types of water bodies